Niveles de resistencia a quinolonas y otros antimicrobianos en cepas de Escherichia coli comensales en niños de la zona periurbana de Lima, Perú - Pons, Maria J (2014)
The main aim of this study was to establish the resistance levels to antimicrobial agents, in 222 non-pathogenic E. Coli strains of fecal origin in Peru. The proportion of resistance found to the evaluated antimicrobials was ampicillin (62.6%), cotrimoxazole (48,6%), tetracycline (43,0%) and chloramphenicol (15,8%). We emphasize the high resistance levels found for quinolones: 32% for nalidixic acid (NAL) and 12% for ciprofloxacin (CIP). These high levels of quinoloneresistance in non-pathogenic strains isolated from children in this age group highlight the extensive use and the impact of the intake of this kind of antimicrobials in the community, showing the potential risk of the loss of their utility in the area.